Good Corporate Governance and Nahdliyah religious value for strengthening Zakat payer trust: case study of Nahdlatul Ulama (NU) community in Indonesia - Santoso, Bedjo; Mohd Israil, Khaliq Ahmad; Wan Jusoh, Wan Noor Hazlina (IP Media Sdn Bhd & Simo Excel PLT, 2024)
The research explores factors influencing Zakat payers' trust in Good Corporate Governance (GCG) principles, specifically the Nahdliyah religious value (NRV) derived from some theories and concepts aiming to address research gaps in Zakat. This research used quantitative methods involving 750 respondents Nahdlatul Ulama (NU) administrators as Zakat payers throughout Indonesia consisting of 552 districts. NU, the largest community in Indonesia, faces low Zakat capability. This research proposes a new concept, combining Social Identity Theory, Resource Advantage Theory, and the origin of NU values, 'Mabaadi Khaira Ummah', to revive the principles towards the best generation and build NRV as novelty. This research identifies four variables that influence the trust of Zakat payers: NRV, GCG elements (accountability - AC, transparency- TR, and credibility - CR). The findings show that AC and TR do not have a real impact to ZPT as they are only significant at the 10% level, but not significant at the 5% level. CR does not affect ZPT. However, the three variables (AC, TR, and CR) affect ZPT if mediated by NRV, which has significant effect on ZPT. Additionally, the results indicate that NRV acts as full mediation, meaning AC, TR, and CR affect ZPT only through NRV. The new concept of NRV is powerful, fills the theoretical gap and offers a new perspective on religious values in the theory of resource superiority and social identity theory as applied in certain religious fields such as Zakat, as an obligation in Islam. NRV addresses relationships between variables and contributes to the development of trust in Zakat. In addition, NRV can be used to trigger the NU community to increase the volume of Zakat.